1969
DOI: 10.1055/s-0028-1095155
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Disturbances in the Male Diabetic Rat

Abstract: Subtotally pancreatectomized (95 %) white male rats do not show sexual disturbances during the prediabetic stage. During the stage of manifest diabetes, disturbances appear, and their severity increases progressively with the duration and degree of hyperglycemia. Fasting blood sugar levels from 120 mg% to 200 mg% are associated with disturbances of sexual behavior, with diminution of insemination capacity , and reduction or abolition of the biosynthesis of androgens in vitro. Blood sugar levels higher than 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 4 publications
0
26
0
Order By: Relevance
“…Some reports in adult rats have suggested a primary testicular disorder as the cause of these alterations [5]. In patients suffering chronic renal failure, an impaired conversion of A to T secondary to low plasma Zn has been reported [13].…”
Section: Discussionmentioning
confidence: 99%
“…Some reports in adult rats have suggested a primary testicular disorder as the cause of these alterations [5]. In patients suffering chronic renal failure, an impaired conversion of A to T secondary to low plasma Zn has been reported [13].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes-associated reproductive dysfunction has been attributed both to alternations in hypothalamo-pituitary and pituitary gonadal activity. Typically, diabetes in the male rat is associated with a decrease in circulating LH (3,8,26) and testosterone (24, 26) levels which undoubtedly account for the : reported reduction in or absence of spermatogenesis (28, 31) and reduction in accessory sex organ weights (7,9,21). A 5HT mechanism within the POA-AH has been implicated as a major regulatory factor in the control of LH secretion in the male rat (17).…”
Section: Discussionmentioning
confidence: 99%
“…They were unable to determine whether the locus for the androgen nonresponsiveness in these diabetic animals is the pituitary gland or hypothalamus. However, other investigators have reported that pituitary gonadotrophin secretion in STZ-induced diabetic rats responds normally to GnRH stimulation (8,22) suggesting that diabetes adversely affects hypothalamic GnRH dis--' _ 60'i . charge.…”
Section: Discussionmentioning
confidence: 99%
“…Withdrawal of insulin during the middle 12 h of conditioning had no significant effect on the quantities of brain cell nuclear estrogen receptors. These results are in agreement with the hypothesis that decreased cell nuclear binding of estradiol by neural target tissues may contribute to the reproductive dysfunctions of diabetics.Impairments of reproductive function as sociated with diabetes mellitus have been doc umented in human beings [10,23] and labora tory animals of both sexes [9,15]. Female rats, made diabetic by subtotal (95%) pancreatec tomy or by selective destruction of pancreatic /(-cells following alloxan or streptozotocin ad ministration, show a variety of reproductive deficits including delayed sexual maturity [15], altered estrous cycles [4,8,16], diminished…”
mentioning
confidence: 99%